2008
DOI: 10.1161/circulationaha.108.769562
|View full text |Cite
|
Sign up to set email alerts
|

Directed and Systematic Differentiation of Cardiovascular Cells From Mouse Induced Pluripotent Stem Cells

Abstract: Background-Induced pluripotent stem (iPS) cells are a novel stem cell population induced from mouse and human adult somatic cells through reprogramming by transduction of defined transcription factors. However, detailed differentiation properties and the directional differentiation system of iPS cells have not been demonstrated. Methods and Results-Previously, we established a novel mouse embryonic stem (ES) cell differentiation system that can reproduce the early differentiation processes of cardiovascular ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
300
1
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 438 publications
(322 citation statements)
references
References 39 publications
13
300
1
6
Order By: Relevance
“…Recently, Narazaki et al [56] succeeded in inducing the differentiation of mouse iPS cells into Flk1 + cardiovascular progenitor cells, which generated arterial, venous and lymphatic endothelial cells, and self-beating cardiomyocytes. Utilization of various TGF-β family members will benefit more efficient differentiation of cardiovascular cells from iPS cells established from patients suffering from cardiovascular diseases.…”
Section: Mesoderm Derivativesmentioning
confidence: 99%
“…Recently, Narazaki et al [56] succeeded in inducing the differentiation of mouse iPS cells into Flk1 + cardiovascular progenitor cells, which generated arterial, venous and lymphatic endothelial cells, and self-beating cardiomyocytes. Utilization of various TGF-β family members will benefit more efficient differentiation of cardiovascular cells from iPS cells established from patients suffering from cardiovascular diseases.…”
Section: Mesoderm Derivativesmentioning
confidence: 99%
“…iPS is an emerging technology where a set of transcriptional factors is introduced via a viral vector into somatic cells such as skin fibroblasts to "induce" pluripotency into them. This technology ideally enables the conversion of terminally differentiated cells into embryonic-stem-like cells that can be differentiated into the desired progeny of cells [17,18]. Work is currently underway into exploring the differentiation potential of these cells into myocardial lineage.…”
Section: Cardiac Tissue Engineeringmentioning
confidence: 99%
“…In 2008, three independent research groups reported the derivation of cardiomyocytes from murine iPSC using embryoid body-based and monolayer-based differentiation protocols [19][20][21]. Later, the capacity for derivation of cardiomyocyte-like cells was demonstrated with human iPSC generated using the 4-gene system (OCT4, SOX2, NANOG, and LIN28 transgenes) [15] and the three-gene system (OCT4, SOX2, and KLF4) plus a histone deacetylase inhibitor (valproic acid) [23].…”
Section: Brief Historical Overview Of the Attempts To Cultivate Rhythmentioning
confidence: 99%